The effect ofWi-Fi signals on the measurement accuracy of electronic apex locator during root canal therapy (Mustansiria Dental Journal, 2018)
Background: The using of devices that emitted electromagnetic radiation has beenlimited in many healthcare centers to prevent interference with medical devices.The purpose of this in vitro study was to evaluate the effect of Wi-Fi Router(Tenda FH456) on working length determination using electronic apex locator(NSK-iPex II) in the presence of network connection with tablet (GT-N800) ornot.Materials and methods: Twenty-five intact teeth with a single root were sectioned atthe cementoenamel junction. Visually, roots were examined understereomicroscope (X20) and the working length was determined using a size 15K-file. The effect of Tenda Wi-Fi router on accuracy of electronic working lengthmeasurement of electronic apex locator (iPex II) was determined in this study inclosed room under 5 conditions (without router and tablet, with router in differentdistances 1 meter and 3 meters from electronic apex locator, with router andconnected with tablet in different distances 1 meter and 3 meters from electronicapex locator). The electronic working length was measured 3 times per canalunder each condition. The data were compared using analysis of variance.Results: The mean of working length measured under microscope was (13.30), andthe mean of working length by electronic apex locator was (13.14) while the meanvalues of working length in different conditions was fixed (13.12). Analysis ofvariance test (ANOVA) showed non-significant difference among working lengthmeasurements in different conditions (P-value ≥ 0.05).Conclusion: Within the limitations of the present study, stability and reliability ofiPex II apex locator in measurement of electronic working length where notinfluenced when placed in (1M, 3M) from Wi-Fi router and active Tablet(connected to network by Wi-Fi and streaming online videos). During root canaltherapy, active Tablet can be used in the dental operatory without the fear ofcausing electromagnetic interference in electronic working length determination.